Descriptions of pupae of five Pimeliinae species (Coleoptera: Tenebrionidae) from Alxa Plateau, China - Shen, Guang-Hui; Zhang, Jian-Ying; Yu, You-Zhi; Ren, Guo-Dong; Jia, Long (Zootaxa, 2026)
The pupal stages of five Pimeliine species occurring in the Alxa Plateau are described and illustrated in detail: Anatolica mucronata Reitter, 1889 (Tentyriini Eschscholtz, 1831), Mantichorula grandis Semenow, 1893 (Pimeliini Latreille, 1802), Trigonocnera pseudopimelia pseudopimelia (Reitter, 1889) (Pimeliini Latreille, 1802), Mantichorula semenowi Reitter, 1889 (Pimeliini Latreille, 1802), and Cyphogenia chinensis (Faldermann, 1835) (Akidini Billberg, 1820).